Safety, nutrition & health in early education - Robertson, Cathie (Thomson Delmar Learning, 2007)
Safety, Nutrition, and Health in Early Education, 3E covers the four major subject areas of safety, nutrition, health, and special topics. New to this edition is expanded coverage of children with disabilities and other special needs; updated information on nutrition, including the new MyPyramid Food Guidance System and practical information on creating linkages with children, families, staff, community, and community resources. Special features of the text include vignettes; checklists; case studies; Pause for Reflection, which offers students a time to pause and examine how they feel about specific topics; Reality Checks with Checkpoints, questions that allow readers to critically examine the information presented; and new tables, charts, photos, and graphics. In addition, special attention is given to bullying; disaster planning for human-generated disasters; how America eats; the impact of war and terrorism on children; Autism; Fetal Alcohol Syndrome; and being at risk for preventable diseases. . This text combines basic information and theory, as well as practical applications, resources, and other early education skills needed for working with children, families, and staff